Encyclopedic dictionary of polymers - Gooch, Jan W. (Jan Woodall) 1946-.; SpringerLink (Online service). (New York Springer, 2011)
This reference, in its second edition, contains more than 7,500 polymeric material terms, including the names of chemicals, processes, formulae, and analytical methods that are used frequently in the polymer and engineering fields. In view of the evolving partnership between physical and life sciences, this title includes an appendix of biochemical and microbiological terms (thus offering previously unpublished material, distinct from all competitors.) Each succinct entry offers a broadly accessible definition as well as cross-references to related terms. Where appropriate to enhance clarity further, the volume's definitions may also offer equations, chemical structures, and other figures. The new interactive software facilitates easy access to a large database of chemical structures (2D/3D-view), audio files for pronunciation, polymer science equations and many more.
Electronic reproduction.
Keywords: Polymers -- Dictionaries; Polymerization -- Dictionaries; Electronic books